Numerical modeling of the conservative exploitation of conventional gas reservoirs. Issue 1 (31st December 2022) - Pérez Rodríguez, Sergio
Abstract: This paper reports the results of a research project aimed at designing heuristically oriented exploitation plans based on simple parameters of static modeling rather than complex ones of dynamic modeling for conventional gas reservoirs. The combined use of heuristic rules relying on the Maximum Efficient Rate (MER) criteria and the Maximum Depletion Rate Model (MDRM, Global Energy Research, Uppsala University) was investigated to model a systemic approach for these reservoirs. Integration of these principles and their comparative evaluation led to findings about their mutual relationships, notably the MER to be regarded as a particular case of the MDRM. The rules rely on a combined use of the exponential version of the Fundamental Equation of Mineral Production (EFE) with the exponential decline (ED) curve analysis. A bridge between the physics of flow in porous media and the Law of Conservation of Matter was found by demonstrating the conditions of equivalence between the ED and the EFE. Production data built upon reservoir characterization of the gas reservoirs supported the comparative analysis. A systematic approach enabled the replication of the material balance-based production profiles by applying a MER-based P/R of 0.08 and a MDRM based of 6 for the plateaus of the wet and dry gas reservoirs, respectively. Production models rested on broadly accurate rules relying on mutual relationships between contemporary volumes of reserves and output yields. The production models reviewed appear useful for a discrete application of the Ockham razor criterion to make relatively effortless modeling of conventional gas reservoir production.